Pragmatics Always Matters: An Expanded Vision of Experimental Pragmatics - Gibbs, Raymond W.; Colston, Herbert L. (Frontiers in Psychology, 2020)
Much of the work in experimental pragmatics is devoted to testing empirical hypotheses that arise within the study of linguistic and philosophical pragmatics. The focus here is often on those aspects of communicated meaning that are “inferred” rather than understood through linguistic “coding” processes. Under this view, pragmatic meanings emerge secondarily after purely linguistic meanings are accessed or computed. Our aim in this article is to greatly broaden the scope of experimental pragmatic studies by calling for much greater emphasis on the complete pragmatics of language use. Pragmatics is continuously present and constrains people’s real-time production and processing of language in context. Experimental pragmatics should attend more to the particularities of pragmatic experience through closer examination of the people we study, the specific tasks used to assess understanding, as well as the actual complex meanings people interpret in diverse contexts..The many specifics of human pragmatics demand the study and theoretical inclusion of many bodily, linguistic, and situational factors that make up each instance of meaning making.